2020
DOI: 10.1093/ibd/izaa162
|View full text |Cite
|
Sign up to set email alerts
|

From the American Epicenter: Coronavirus Disease 2019 in Patients with Inflammatory Bowel Disease in the New York City Metropolitan Area

Abstract: Background We aimed to characterize patients with inflammatory bowel disease (IBD) and novel coronavirus disease 2019 (COVID-19). Methods We performed a case series of patients with IBD and confirmed or highly suspected COVID-19 to assess rates of severe outcomes. Results We identified 83 patients with IBD with confirmed (54%) or highly suspected (46%) COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 6 publications
8
36
0
Order By: Relevance
“…IBD patients with COVID‐19 were no more likely to attain the composite outcome of hospital admission or death within 30 days following a diagnosis of COVID‐19 compared to non‐IBD‐patients with COVID‐19 (relative risk = 0.93; 95% CI = 0.68–1.27). This is consistent with smaller well‐characterised studies from IBD centres 17 . Still, none of these studies calculated relative risks for incident or severe COVID‐19 in IBD versus matched general population controls.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…IBD patients with COVID‐19 were no more likely to attain the composite outcome of hospital admission or death within 30 days following a diagnosis of COVID‐19 compared to non‐IBD‐patients with COVID‐19 (relative risk = 0.93; 95% CI = 0.68–1.27). This is consistent with smaller well‐characterised studies from IBD centres 17 . Still, none of these studies calculated relative risks for incident or severe COVID‐19 in IBD versus matched general population controls.…”
Section: Introductionsupporting
confidence: 82%
“…Research on IBD and COVID-19 evolved from how to manage patients during the pandemic, [29][30][31][32] followed by patient series from larger centres with COVID-19, 17,33,34 and research on risk factors for COVID-19 or severe COVID-19 in the IBD patient population. 35,36 A recent Danish study by Attauabi et al 14 In the present study, and differing from earlier research, we neither restricted our population exclusively to IBD patients nor to patients who are COVID-19 positive.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Axelrad et al, 1 which reported that patients with inflammatory bowel disease (IBD) are not at increased risk of COVID-19 and that immunosuppression did not modify the risk of severe outcomes, as previously suggested. 2 , 3 Some authors have even hypothesized that biologics have a protective effect against SARS-CoV-2 infection, 4 , 5 although it is also possible that the lack of increased risk is because patients with IBD spontaneously adopt more rigorous self-protecting measures.…”
mentioning
confidence: 75%
“…3 Patients may also present with gastrointestinal (GI) symptoms including diarrhea, nausea and vomiting, loss of taste and smell. 4,5 The increased GI symptoms are thought to be angiotensin-converting enzyme-2 (ACE2) receptor mediated changes by the SARS-CoV-2 which is present throughout the gut mucosa in predominance. 6 In the absence of typical symptoms, it is difficult to differentiate these GI symptoms due to COVID-19 infection or due to disease flare.…”
mentioning
confidence: 99%